Giancarlo De Carlo and participation: The case of the villaggio Matteotti. Terni, Italy - Franchini, Alberto (2022)
The description of the process of participation of the users of the villaggio Matteotti is toured through the different moments and various ways in which it is carried out: questionnaires, interviews, debates, publications, exhibitions, guided tours. The narration of the events, which are followed for six years from the establishment of the urban study to the delivery of the departments, seeks to clarify the effective power of decision of the users and how their needs influence in the building finally constructed. This history cannot go without the spaces of the previous complex, the clients, the inhabitants, the managers, the financing programs for the workers, the state companies involved in the construction or the contributions of the sociologist, the curator and the graphic designer of the exhibitions, as well as the company’s magazines or the support of the operators.